ANALISIS FAKTOR BUDAYA, SOSIAL, PRIBADI DAN PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN PRODUK AIR MINUM DALAM KEMASAN MEREK VIRO DI KOTA BOGOR - Fahrudin, M Ihsan; Samsuri, Samsuri (Fakultas Ekonomi Universitas Djuanda, 2015)
This study aims to identify and analyze that cultural factors, social, personal and psychological berpengaru the decision of buying bottled water brand in the city of Bogor viro either simultaneously or partially. Analysis method used is descriptive ananlisis method, the method comprising the analysis statistical multiple linear regression analysis, significant testing and testing singnifikan simultaneous partial and determination coefficient testing and statistical test (F test and t test). From vaildtas and reliability test results showed that all the questions declared valid and reliable. Based on the results of the research results of the coefficient of determination (R2) of 56.9%, which means that the influence of cultural, social, personal, and psychological on purchasing decisions bottled water brand viro in Bogor. While the remaining 43.1% is explained in another variable models. Simultaneously cultural, social, personal, and psychological influence on purchase decisions inum water in viro brand packaging. Furthermore, the partial showed that culture, personal and psychological significant effect on the purchase decision inum water in viro brand packaging.Keywords: Cultural, social, personal and psychological, purchasing decisions